Pengendalian Kualitas Untuk Meminimumkan kecacatan Produk Sprocket - Wijaya, Aditya; Mundari, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
PT. XYZ is a company engaged in the manufacturing sector (manufacturing automotive spare parts) with a production process using fine blanking machines and international standard press machines. Based on the data obtained, related to product quality, there are problems that occur during the production process and product results. These problems are related to the level of defects in the production process. From historical production data from July to November 2022, sprocket products contribute the most defective products, both congenital physical defects of the material itself and during the production process such as dakon, scratch, crack/hadan, and burry, which can affect the quality specifications that have been set with a tolerance limit of 0.4%. In general, defective sprocket products can still be reworked, but it takes a long time, so the company will be greatly disadvantaged because production costs will soar. Therefore, based on these problems, the researcher uses the American Military Standard (Mill STD 105D) and American Military Standard (Mill STD 414) methods, which aim to look at aspects of the causes of defects, the level of defects on sprockets, and provide advice to companies on how to minimize sprocket product failure. Based on the results of research conducted on quality control planning using this method, it is known that the results of inspection can be accepted as passing when the number of variable defects is less than 6 pcs in 13 pcs for major defects, while minor defects can be accepted as passing when the number of attribute defects is less than 15 pcs in 200 pcs.